Mental Health Disturbance after a Major Earthquake in Northern Peru: A Preliminary, Cross-Sectional Study - Valladares-Garrido, Mario J. (2022)
Little has been studied in Peru on the mental health repercussions after a major earthquake.We aimed to explore the factors associated with depressive and anxiety symptoms in people whoexperienced a 6.1 magnitude earthquake in Piura, Peru, on 30 July 2021. A preliminary cross-sectional study was conducted in the general population between August–September 2021. An onlinequestionnaire was provided using PHQ-9, GAD-7, and other relevant measures. Generalized linearmodels were applied. Of the 177 participants, the median age was 22 years, the majority were female(56%), and many experienced depressive (52%) or anxiety symptoms (52%). Presence of depressivesymptoms was associated with a personal history of mental disorder, moderate housing damage,social/material support from politicians, moderate food insecurity, and insomnia. Presence of anxietysymptoms was associated with physical injury caused by the earthquake, mild food insecurity, andinsomnia. The development of depressive and anxiety symptoms following the 2021 earthquakeexperienced in Piura depended on multiple individual and socioeconomic factors. Additional studiesshould reinforce the factors identified here given the methodological limitations, such as the studydesign, sampling method, and sample size. This would lead to effective intervention measures tomitigate the impact of earthquakes on mental health.